Pengembangan Bahan Ajar Interaktif Ekonomi Berbasis Teknologi Untuk Generasi Z - Inarwati (CV. SINAR HOWUHOWU, 2025)
The rapid development of digital technology has significantly influenced the education sector, particularly in the learning process of economics. Generation Z, known as digital natives, prefers interactive, visual, and technology-based learning experiences over conventional methods. This research aims to develop an interactive technology-based economics learning material tailored for Generation Z and to examine its effectiveness in improving student engagement and learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE model, involving needs analysis, design, development, validation, implementation, and evaluation. Data were collected through questionnaires, interviews, observations, and documentation, with validation conducted by subject matter experts and media experts. The findings show that the developed material was rated as highly feasible, with positive responses from both experts and students. Trial results indicate that 85% of students reported increased motivation, and an average improvement of 18% was observed in formative test scores. Moreover, the interactive material facilitated the development of 21st-century skills, such as critical thinking, problem-solving, and digital literacy. In conclusion, the integration of technology in economics education is not only relevant but also necessary to meet the learning needs of Generation Z. This study contributes to the advancement of modern teaching strategies and provides implications for the wider application of digital-based learning in various subjects.